2014
DOI: 10.1371/journal.pone.0113950
|View full text |Cite
|
Sign up to set email alerts
|

Regucalcin Expression in Bovine Tissues and Its Regulation by Sex Steroid Hormones in Accessory Sex Glands

Abstract: Regucalcin (RGN) is a mammalian Ca2+-binding protein that plays an important role in intracellular Ca2+ homeostasis. Recently, RGN has been identified as a target gene for sex steroid hormones in the prostate glands and testis of rats and humans, but no studies have focused on RGN expression in bovine tissues. Thus, in the present study, we examined RGN mRNA and protein expression in the different tissues and organs of veal calves and beef cattle. Moreover, we investigated whether RGN expression is controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 87 publications
(95 reference statements)
8
11
0
Order By: Relevance
“…Nevertheless, other factors must be involved in the diminution of RGN levels in PCa, since androgen-insensitive PC3 cells also displayed reduced expression of RGN. Taking into account the present findings, and our previous data indicating RGN as an androgen-responsive gene [14,19,20] o in rat and mice liver, with RGN mRNA being markedly increased at 30 and 60 min after intraperitoneal administration of CaCl 2 [21,22], or between 30 and 180 min following a single oral administration of CaCl 2 solution [23]. The stimulatory effect on RGN concentration was also described in the rat kidney cortex 60 to 120 min after of a single intraperitoneal administration of a CaCl 2 solution [24].…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, other factors must be involved in the diminution of RGN levels in PCa, since androgen-insensitive PC3 cells also displayed reduced expression of RGN. Taking into account the present findings, and our previous data indicating RGN as an androgen-responsive gene [14,19,20] o in rat and mice liver, with RGN mRNA being markedly increased at 30 and 60 min after intraperitoneal administration of CaCl 2 [21,22], or between 30 and 180 min following a single oral administration of CaCl 2 solution [23]. The stimulatory effect on RGN concentration was also described in the rat kidney cortex 60 to 120 min after of a single intraperitoneal administration of a CaCl 2 solution [24].…”
Section: Discussionsupporting
confidence: 82%
“…The immunocytological study suggests the localization of RGN in the acrosomal region of ejaculated buffalo spermatozoa. There have been reports of the localization of RGN protein in germ cells, mainly in the cytoplasm and weakly in the nucleus of rat and human testis (Laurentino et al, 2011), whereas it was only weakly in nuclei in bovine testes (Cucuzza et al, 2014). Our previous study also demonstrated the localization of RGN mainly in cytoplasm and weakly in nucleus of buffalo germ cells (Harikrishna, Shende, Parmar, et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…Noteworthy, RGN expression in all testicular cell types in rat, human and bovine was confirmed by PCR, Western blot and immunohistochemistry (Cucuzza, Divari, Mulasso, Biolatti, & Cannizzo, 2014;Laurentino et al, 2011). Additionally, it is detected in accessory sex glands namely seminal vesicles, bulbourethral and prostate glands of male reproductive tract of the rat, bovine and human (Cucuzza et al, 2014;Laurentino et al, 2011) and also in seminiferous tubule fluid (Laurentino et al, 2011), epididymal fluid (Laurentino et al, 2011) and in seminal vesicular fluid (Harikrishna, Shende, Reena, Thomas, & Bhure, 2016;Harikrishna, Shende, Parmar, et al, 2016). Its wide distribution in male reproductive tissues and in their secretions suggests an important role of this protein in male reproduction.…”
Section: Introductionmentioning
confidence: 84%
“…Steroid hormones and their receptors play multiple roles in the regulation of biological functions, including sex organ development, pregnancy, bone density, cholesterol mobilization, brain function, cardiovascular system, and more. [1][2][3][4][5] They play an important role in breast cancer development and progression. Almost 70% of breast cancers are hormone receptor-positive.…”
Section: Introductionmentioning
confidence: 99%